Pengembangan Bahan Ajar Ilmu Balaghah yang Berbasiskan Uslub Al Qur’an di Prodi PBA FAI-UIR - Rohman, Taufik; Supriady, Harif (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
Balaghah is one of the branches of Arabic knowledge that must be mastered by Arabic language learners, where the study focuses on the meanings of Arabic so that diction and expressions can be in accordance with the situation and conditions in which the conversation takes place, However, the obstacle faced by students is the difficulty of understanding the learning material, most of the examples used are Arabic poetry, for students with a non-pesastren background, this is certainly a difficult thing. This research was carried out with the aim of developing teaching materials for Balaghah Science by using the Qur'anic expression pattern approach. The method used in this study is Research and Development research with a qualitative approach, the development model used is the Design-Based Research (DBR) model, which is a research approach that is very oriented towards developing practical solutions to deal with concrete problems in the world of education. The author's data collection techniques used observation, interviews, documentation and focused group discussions.